Application of a thermodynamic concept for the analysis of structural degradation of soap thickened lubricating greases - Erik Kuhn (Lubricants : open access journal, 2018)
Lubricating greases are special lubricants with a wide range of application. The tribologically stressed grease is used as tribological system and finally modeled as an open thermodynamic system. This study investigated the phenomenon of self-optimization and applied to the process of shearing a grease. The conditions for self-optimization and the consequences of created dissipative structures are investigated according to the interpreted literature.
Keywords: Entropy production; Liquid friction; Lubricating greases; Structural degradation